2009
DOI: 10.1057/jos.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

Success and failure in the simulation of an Accident and Emergency department

Abstract: Healthcare simulation has the potential to offer many benefits but the implementation is often problematic. This paper describes the development of a simulation of an Accident and Emergency Department in an NHS hospital. The early experience of the client provoked great enthusiasm but ultimately the simulation failed to meet all expectations. The simulation delivered a number of benefits, notably in terms of stimulating constructive debate and helping the stakeholders appreciate the complete Accident and Emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…As such, the time needed for detailed modelling (and associated data collection) to make an impact is rarely available. This is similar to the experience of Bowers et al (2009) who found initial 'simple' analyses and work useful for an ED, but the time needed for more complex M&S meant that delivery was too late for impact. The literature on the M&S of ED's is extensive, as illustrated by a recent reviews (Gul and Guneri 2015;Saghafian et al 2015).…”
Section: Where Next For Ed Simulation?supporting
confidence: 64%
“…As such, the time needed for detailed modelling (and associated data collection) to make an impact is rarely available. This is similar to the experience of Bowers et al (2009) who found initial 'simple' analyses and work useful for an ED, but the time needed for more complex M&S meant that delivery was too late for impact. The literature on the M&S of ED's is extensive, as illustrated by a recent reviews (Gul and Guneri 2015;Saghafian et al 2015).…”
Section: Where Next For Ed Simulation?supporting
confidence: 64%
“…This poses a major modelling challenge: simulating the whole hospital is one approach but more commonly A&E simulations strive to capture the critical characteristics of these interactions without a commitment to producing a model of the whole hospital in detail. The NHS Fife A&E simulation has been described elsewhere (Bowers et al, 2009); the summary below focuses on the contribution of the simulation to the redesign process and the relationship with the client.…”
Section: Simulation Of Accident and Emergency Care In Nhs Fifementioning
confidence: 99%
“…A review of this literature reveals that only 6 of the papers even make mention of the 4-hour standard (Codrington-Virtue et al 2006;Gunal and Pidd 2006;Bowers, Ghattas and Mould 2009;Gunal and Pidd 2009;Maulla et al 2009) and of these only two include it in their analysis of the throughput times. Maulla et al (2009) conclude that "…it is not a case of medical staff misreporting the LoS [Length of Stay] but of adapting their behaviour to meet the 4 h target" while Gunal and Pidd (2009) state "…it is reasonable to suppose that the looming breach point caused the department to find ways to quickly complete the processing of a small proportion of their patients."…”
Section: Literature Reviewmentioning
confidence: 99%